(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putra SRT, Trisnawati I. 2024. Short Communication: Habitat preferences of epiphytic orchids and potential pollinators in Sumber Pawon Forest, Kediri District, East Java, Indonesia. Biodiversitas 25: 2780-2787. Sumber Pawon Forest, a unique and biodiverse ecosystem in Kediri, Indonesia, is home to approximately 30,000 orchids (family Orchidaceae), which can grow terrestrial or as epiphytes. A diversity of different taxa has been recorded as orchid pollinators. The distribution of epiphytic orchids in this forest is determined by habitat preferences including vertical distribution zone and host tree’s characteristics. This research, conducted in the captivating Sumber Pawon Forest, aims to determine habitat preferences influencing the abundance of epiphytic orchids and provide a review of potential epiphytic orchid pollinators. The data were collected by systematic sampling method. Analysis of epiphytic orchids’ habitat preferences was done using the ordination method. The study found 3 epiphytic orchids and 5 species of host trees, revealing new insights into their distribution. Epiphytic orchids include Cymbidium sp., Dendrobium crumenatum, and Rhynchostylis retusa. The host trees include Alstonia scholaris, Artocarpus elasticus, Bischofia javanica, Ficus elastica, and Samanea saman. Epiphytic orchids were mainly found in zone 4 rather than in zone 5. The characteristics of host trees, which are preferentially selected by epiphytic orchids, include tree height (ranging from 28.65 to 33.65 m), large DBH (ranging from 165.61 to 175.80 m), and closed canopy cover (ranging from 51 to 75%). One of the pollinator taxa (named Hymenoptera) was found to pollinate epiphytic orchid species, adding to our understanding of their ecological interactions.